Ternary Polymer Solar Cells based on Two Acceptors and One Donor for Achieving 12.2% Efficiency - Zhao, Wenchao (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.